How Poetry Improves EFL Learners’ Vocabulary through Curriculum-based Dynamic Assessment - Ali Imron; Winda Candra Hantari (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2021)
Literature in English teaching has always been interested to be discussed, specifically in teaching English for speakers of other languages (TESOL) or teaching English as Foreign Language (TEFL). This research aimed to reveal the effectiveness of Poetry as a genre in Literature in TESOL or TEFL for students of English Education Study Program to improve students’ writing skills. Delivered using Curriculum-based Dynamic Assessment with the focus on the process of Mediated Learning Experience and simplified Vocabulary Knowledge Scale test, the results show that Poetry as a genre in Literature is effective in improving students’ writing skills in two aspects; (1) it strengthens students’ motivation and creative thinking as it generates and involves students’ emotion, and (2) it improves students’ vocabulary mastery seen from the improvement of the diction in their writings by 336,25%.